Green Innovation, Carbon Storage and Perceived environmental quality in Lagos State University, Nigeria - Ogundele, Fatai Olakunle; Olatunji-Bello, Ibiyemi Ibilola; Adeneye, Adejuwon Adewale (Journal of Sustainability Perspectives, 2023)
A sustainable university has been defined as a higher educational institution that addresses, involves and promotes the minimization of negative environmental, economic, societal, and health effects generated in the use of their resources in order to fulfil its functions of teaching, research, outreach and partnership, and stewardship in ways to help society make the transition to sustainable lifestyles. Earlier studies on green innovations have basically centered on the environmental benefits and were purely descriptive in nature. Several others examined the effect of green innovation on soil organic carbon by comparing street trees of species. The present study would contribute to literature using a mixed research approach to empirically investigate the contributions of green innovation on carbon storage and perceived environmental quality in Lagos State University, Nigeria. Data for the study were obtained by collecting 100 surface (0 – 15cm) soil samples with the aid of a soil auger under campus trees, grasses, ornamental trees and vegetables (Amaranthus and green vegetable farms) across different land uses on campus. Also, data on green characteristics (tree height, tree size, canopy cover, density of herbs, basal cover and herbaceous cover) were measured using different ecological procedures, while 655 questionnaire copies were administered to staff and students to ascertain their perceived environmental quality of green innovation. Data obtained were analyzed using averages, simple percentages, One-Way Analysis of Variance, multiple regression analysis and principal components analysis. The results obtained showed that carbon storage significantly varied among the green innovation components with canopy cover contributing over 55% of carbon storage. The study revealed that canopy cover and tree size substantially contributed in carbon storage with canopy cover being more effective. PCA result identified beautification of LASU (19.8%), flood control (18.8%), promotion of urban ecology (15.8%) and improvement in air quality (9.5%) as the principal dimensions or perceived environmental quality of green innovation. The result further showed that green innovation characteristics have significant relationship with carbon storage. The study shows the importance of campus tree in carbon reduction and recommends the need for universities to give necessary recognition and incorporate these green components in physical planning.